ORGANIZATION CULTURE AND LECTURER PERFORMANCE : CASE OF PAPUA PRIVATE UNIVERSITIES - Ferdinandus Christian (International Journal of Economics Management and Social Science, 2018)
This study aims to determine the influence of organizational culture on the performance of lecturers of private university in Papua. This study includes the type of survey research and the method of research is utilizes the questionnaire in the main data collection in this case is the primary data of a number of samples from the population. In general, which is the unit of analysis in this survey research is individual. The results showed that organizational culture had a positive and significant effect on lecturer performance as evidenced by CR value of 1,998 and P 0.047 and the results were in accordance with the research hypothesis.